Designing hybrid nanoparticles - Benelmekki, Maria (IOP ebooks, 2021)
This research text provides a concise overview of the technical approaches to the synthesis and characterization of hybrid nanoparticles, with a focus on one of the most promising 'bottom-up' techniques for designing tailored hybrid nanoparticles based on the practical magnetron-sputtering inert-gas-condensation (MS-IGC) method. A modified MS-IGC system is presented, and its performance under different conditions is evaluated. This fully revised second edition provides the latest developments in the design and characterization of hybrid nanoparticles produced by gas phase methods and includes a new chapter that explains how the design of the modified magnetron-sputtering inert-gas-condensation system is contributing to the shape transformation of nanoparticles (0D) to form nanorods (1D) with different aspect ratios.- Resumé vydavatel